A review on an imperative by-product: Glycosaminoglycans- A holistic approach - Bindia Sahu; Diya Deepak Sharma; Gladstone Christopher Jayakumar; Balaraman Madhan; Farhan Zameer (Carbohydrate Polymer Technologies and Applications, 2023)
Glycosaminoglycan is a generic term for a class of minor but significant components of the body. The extraction, application, and functionalization of GAGs are essential to explore owing to their biological significance. The extraction of GAGs from different species, such as vertebrates, invertebrates, molluscs, and marine sources, is discussed. The present review focuses on the GAGs extraction and purification by various techniques like spectroscopic, chromatographic, and enzymatic methods. The review also emphasizes the functionalities of glycosaminoglycans and their mode of interaction with the protein moiety for their physiological functions. The industrial applications of GAGs in various areas, such as cosmetics, medicine, biotechnology, food, and textiles, have also been reported in the present review.